A Drosophila model of Fragile X syndrome exhibits defects in phagocytosis by innate immune cells. - O'Connor, R.M.; Stone, E.F.; Wayne, C.R.; Marcinkevicius, E.V.; Ulgherait, M.; Delventhal, R.; Pantalia, M.M.; Hill, V.M.; Zhou, C.G.; McAllister, S.; Chen, A.; Ziegenfuss, J.S.; et al. (Journal of Cell Biology, 2017)
Fragile X syndrome, the most common known monogenic cause of autism, results from the loss of FMR1, a conserved, ubiquitously expressed RNA-binding protein. Recent evidence suggests that Fragile X syndrome and other types of autism are associated with immune system defects. We found that Drosophila melanogaster Fmr1 mutants exhibit increased sensitivity to bacterial infection and decreased phagocytosis of bacteria by systemic immune cells. Using tissue-specific RNAi-mediated knockdown, we showed that Fmr1 plays a cell-autonomous role in the phagocytosis of bacteria. Fmr1 mutants also exhibit delays in two processes that require phagocytosis by glial cells, the immune cells in the brain: neuronal clearance after injury in adults and the development of the mushroom body, a brain structure required for learning and memory. Delayed neuronal clearance is associated with reduced recruitment of activated glia to the site of injury. These results suggest a previously unrecognized role for Fmr1 in regulating the activation of phagocytic immune cells both in the body and the brain.